The descending pain modulation system predicts short term efficacy of multimodal pain therapy: an observational prospective cohort study. Issue 3 (3rd April 2022) - Sendel, M; Lienau, F; Fischer, D; Moll, J; Koch, S; Forstenpointner, J; Binder, A; Baron, R
ABSTRACT: Objectives: Treating chronic pain patients with multimodal pain therapy (MMPT) alters perception, awareness, and processing of pain at multiple therapeutic levels. Several clinical observations suggest that the effects of therapy may go beyond the possible sum of each level of therapy and may be due to a central descending inhibitory effect measurable by conditioned pain modulation (CPM). Thus, we investigated whether CPM is able to identify a group of patients that benefit particularly from MMPT. Methods: This was an observational prospective cohort study. Patients were hospitalized on a special pain medicine ward with specially trained staff for 10 days. The patients were questioned and had investigations before and shortly after MMPT and were followed-up on 3 months post discharge. Before and after treatment, subjects were investigated via CPM and quantitative sensory testing (QST) as well as completing questionnaires. The study was registered in the German Clinical Trials Register (DRKS00006850). Results: During the study period of 24 months, 224 chronic pain patients were recruited. 51 percent of patients completed the study period. There was an improvement in overall groups regarding all domains assessed, lasting beyond the end of the intervention. Patients with a sufficient CPM effect, defined as a reduction in pain during the conditioning stimulus, at baseline did show a more pronounced reduction in mean pain ratings than those without. This was not the case 3 months after therapy. Furthermore, sufficient CPM was identified as a predictor for pain reduction using a linear regression model. Conclusion: In conclusion, this study shows that while a heterogeneous group of patients with chronic pain disorders does sustainably benefit from MMPT in general, patients with a sufficient CPM effect do show a more pronounced decrease in pain ratings directly after therapy in comparison to those without. PLAIN LANGUAGE SUMMARY: Pain at one body site can be reduced, when another painful stimulus occurs at the same time. This mechanism is referred to as conditioned pain modulation (CPM). Some patients with chronic pain are treated using different methods such as medication, physiotherapy, and patient education in an in-patient setting, referred to as multimodal pain therapy (MMST). To improve pain therapy, it is vital to identify whether patients who respond especially well to a certain treatment show specific characteristics (i.e. mechanism-based therapy). We investigated whether the prospect of success of MMST is related to how well CPM works in patients. We assessed the CPM effect and sensory function of 224 patients with chronic pain before and after therapy to answer this question. Additionally, patients completed questionnaires about their pain, mood, quality of life, and sleep directly after therapy and three months later. All patients showed improvement after therapy, but in those in which CPM worked well, pain was reduced stronger than in those in which CPM did not. Three months after treatment, the difference disappeared.